A gender and industry-responsive curriculum model for technical-vocational teacher education program - Alinea, Jess Mark L.; Reyes, Wilma S. (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2023)
The study aimed to determine the gender and industry-practice gaps in the Technical-Vocational Teacher Education (TVTEd) program and fill these gaps through a curriculum model to make TVTEd gender and industry-responsive. The study used a mixed method approach where quantitative and qualitative data were utilized to develop the curriculum model. Phase 1 is quantitative descriptive research that focuses on the adequacy and usefulness of the pedagogical and technical skills of the curriculum using the lenses of TVTEd graduates and their supervisors. Phases 2 is a literature review that mapped the gender and industry-practice gaps in TVET. Phase 3 is a qualitative case study research focused on identifying the emerging gender issues constraining gender-responsive curriculum practices. Participants for Phase 1 were seventy-one (71) TVTEd graduates and thirty (30) academic and industry supervisors. Phase 2 scrutinized fifty-five (55) related studies. Participants of the Phase 3 included six (6) technical professors, seven (7) TVTEd graduates, and twelve (12) TVTEd students. Quantitative data were analyzed using statistical treatment (mean score, standard deviation, and weighted mean) and qualitative data were thematized using inductive thematic analysis. The results of the study showed a disparity in the technical skills of the TVTEd graduates, emerging gender and industry-practice gaps in the literature, and contradictions in the subjects (teachers), rules, tools, community, division of labor, and object within the activity system of TVTEd. The consolidated inputs from the four phases of the study were analyzed and utilized in developing a gender and industry-responsive curriculum model for TVTEd.